Public Debt: What Measures Should We Use? A Case Study of Public Debt in Mid‐ and Post‐pandemic Australia and Its Economic, Policy and Social Consequences. (2nd September 2022) - Zwalf, Sebastian; Scott, Robin
Abstract: The COVID‐19 pandemic saw governments around the world suddenly accumulate substantially higher levels of public debt. We consider the level of debt entered into by Australia's federal, state and territory governments and compare this against three metrics for debt sustainability. Using these measures, we find that current and future public debt levels sit within what is regarded as sustainable by scholarly and practitioner opinion. However, we note that recent increases in interest rates will challenge this. We conclude by outlining a range of economic, social and policy challenges arising from the new high public debt environment.